PERAN KOMISI PERLINDUNGAN ANAK INDONESIA (KPAI) DALAM PENANGANAN KASUS KEKERASAN TERHADAP ANAK - Achmad Sumali; Eko Handoyo; Edi Waluyo (STKIP Subang, 2026)
Child violence remains a serious problem in Indonesia that requires comprehensive handling from various parties. The Indonesian Child Protection Commission (KPAI) as a state institution has a strategic role in supervising, monitoring, and advocating for children's rights. This study aims to describe and analyze the role of KPAI in handling cases of violence against children in Indonesia. Using qualitative descriptive research methods through library research, data was collected from official KPAI documents, government regulations, journal articles, and relevant reference books. The results show that KPAI's role covers three main dimensions: (1) supervision and monitoring of child protection policies; (2) mediation and case handling through an integrated complaint system; and (3) advocacy, socialization, and collaboration with related agencies. However, in its implementation, KPAI faces significant challenges including limited authority, inadequate human resources, and weak coordination between institutions. This study concludes that strengthening KPAI's institutional capacity and synergy between government, society, and family is essential for effective child protection in Indonesia.